2008
DOI: 10.1080/08820130802111605
|View full text |Cite
|
Sign up to set email alerts
|

HLA-Class II Alleles in Egyptian Patients with Hepatocellular Carcinoma

Abstract: 1. A significantly increased frequency of DRB1*04, and DQB1 *02 in HCC patients versus control group (p = 0.016, and 0.032, respectively) was found; 2. A significantly decreased frequency of DQB1*06 (p = 0.032) was found; 3. A significantly increased frequency of DRB1*07 (odds ratio (OR) = 4.929) was found; and 4. A significantly decreased frequency of DRB1*15 (OR = 0.316) was seen. In conclusion, while some alleles are significantly associated with HCC (DRB1*04, DQB1*02) and others are not associated (DQB1*06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…For analysis, liver fibrosis was also classified either being mild (0-2), moderate (3)(4) or severe (5-6). Activity was graded into minimal (0-4), mild (5-8), moderate (8)(9)(10)(11)(12) and severe (13)(14)(15)(16)(17)(18)). All patients were tested negative for both hepatitis B surface antigen (HBs antigen) and anti-HIV antibody.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For analysis, liver fibrosis was also classified either being mild (0-2), moderate (3)(4) or severe (5-6). Activity was graded into minimal (0-4), mild (5-8), moderate (8)(9)(10)(11)(12) and severe (13)(14)(15)(16)(17)(18)). All patients were tested negative for both hepatitis B surface antigen (HBs antigen) and anti-HIV antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Because the prevalence of HCV is exceeding that of hepatitis B virus (HBV) infection, HCV infection has become the leading risk factor for HCC in Egypt (antibodies present in as many as 75-90% of HCC cases) [9,10]. The frequency of liver-related cancers (>95% as HCC) relative to all cancers in Egypt has increased from approximately 4.0% in 1993 to 7.3% in 2003 [11].…”
Section: Introductionmentioning
confidence: 99%
“…A high a significant difference between DQB1*02 and metavir score(F and A) was observed for that a lot of study associated between DQB1*02 with Hepatocellular Carcinoma as El-Chennawi et al (2008) concluded that the DRB1*04 and DQB1*02 alleles might be risk factors for the occurrence of HCC also found DQB1*02 to be associated with disease persistence even after IFN. The present study also investigated the effect of Interleukin (IL)-10 level on response to treatment and its relation with disease state.…”
Section: Discussionmentioning
confidence: 97%
“…El-Chennawi et al 12 studied the association of hla class ii DRB1 and DQB1 polymorphisms with hcc in Egyptian patients and investigated the role of those polymorphisms as risk factors for the development of hcc. Those authors found a significantly increased frequency of DRB1*04 and DQB1*02 (p = 0.016 and 0.032 respectively) and a significantly decreased frequency of DQB1*06 (p = 0.032) in their hcc patients compared with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many genetic factors have been reported to be related to a susceptibility to hcc: polymorphisms of tumour necrosis factor α 6,7 , of epidermal growth factor and epidermal growth factor receptor 8,9 , of the transforming growth factor β1 gene 10 , and of major histocompatibility complex (mhc) or human leucocyte antigen (hla) [11][12][13][14][15] , among others. Of the foregoing genetic factors, mhc plays a key role in antivirus activity and tumour defense.…”
Section: Introductionmentioning
confidence: 99%